The Effect of Social Care Support for Children on Women's Fertility Intentions - Cai, Xinmei (International Journal of Global Economics and Management, 2024)
In recent years, in order to alleviate the pressure of population aging, China has actively promoted the policy of encouraging childbirth, but China is still in a period of low fertility. In this context, this paper uses the data of the 2020 China Family Longitudinal Survey (CFPS) to explore the impact of children's social care on women's fertility intention. The results show that participation in social care does not increase women's fertility intentions, but further discourages women from having children, and this situation affects women living in rural areas more obviously. Accordingly, it is particularly important to strengthen the construction of the social care system for children, reduce the pressure on women's families, and enable women of childbearing age to release more reproductive potential.